On short cracks that depart from elastoplastic notch tips - Verônica Miquelin Machado; Jaime Tupiassú Pinho de Castro; Marco Antonio Meggiolaro (Fracture and Structural Integrity)
The behavior of short cracks that depart from elastoplastic notch tips is modeled to estimate the stresses required to initiate and to propagate cracks in notched structural components, and to evaluate the size of tolerable crack-like defects under general loading conditions. This analysis can model both fatigue and environmentally assisted cracking problems; can evaluate notch sensitivity in both cases; and can as well be used to establish design or acceptance criteria for tolerable non-propagating crack-like defects in such cases. The growth of short cracks is assumed driven by the applied stresses and by the stress gradient ahead the notch tip, and supported by the material resistances to crack initiation and to long crack propagation by fatigue or EAC. In the elastoplastic case, the stress gradient ahead of the notch tip is quantified by a J-field to consider the short crack behavior. The tolerable short crack predictions made by this model are evaluated by suitable fatigue and EAC tests of notched specimens specially designed to start nonpropagating cracks from the notch tips, both under elastic and elastoplastic conditions.